Effectiveness of current psychological interventions to improve emotion regulation in youth: a meta-analysis - Moltrecht, B; Deighton, J; Patalay, P; Edbrooke-Childs, J (Springer, 2020)
Research investigating the role of emotion regulation (ER) in the development and treatment of psychopathology has increased in recent years. Evidence suggests that an increased focus on ER in treatment can improve existing interventions. Most ER research has neglected young people, therefore the present meta-analysis summarizes the evidence for existing psychosocial intervention and their effectiveness to improve ER in youth. A systematic review and meta-analysis was conducted according to the PRISMA guidelines. Twenty-one randomized-control-trials (RCTs) assessed changes in ER following a psychological intervention in youth exhibiting various psychopathological symptoms. We found moderate effect sizes for current interventions to decrease emotion dysregulation in youth (g = − 0.46) and small effect sizes to improve emotion regulation (g = 0.36). Significant differences between studies including intervention components, ER measures and populations studied resulted in large heterogeneity. This is the first meta-analysis that summarizes the effectiveness for existing interventions to improve ER in youth. The results suggest that interventions can enhance ER in youth, and that these improvements correlate with improvements in psychopathology. More RCTs including larger sample sizes, different age groups and psychopathologies are needed to increase our understanding of what works for who and when.